(untitled) (Conversatoria Linguistica, 2018)
The paper describes lexical bundles (Biber 1996) occurring in research medical texts. Two corpora of medical texts are used to analyse lexical bundles both qualitatively and quantitatively: a corpus of articles published in Polish journals and a corpus of texts published in British journals (largely in the British Medical Journal). The investigation reveals that referential lexical bundles are prevalent in both corpora. No significant differences can be observed between the two corpora, yet there is a tendency